Financial Capability and Digital Adoption for Online Shopping Decision: Evidence from Surabaya Students - Kartikasari, Cynthia Yohanna; Prasetyowatie, Yohana Wahyu (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
This study aims to examine the effect of financial capabilities and digital adoption on online shopping decisions. The research results explain that individual financial capabilities such as access to bank services, digital banking services, and consulting financial issues with professionals encourage online shopping transactions. Online consumer behavior is also determined by perceived risk, trust in service providers, technology adoption, and use of social media. The type of research was quantitative by interviewing random sampling Surabaya students. Data analysis used multiple linear regression tests through validity test in terms of determining the feasibility of the questions in the questionnaire and reliability test, which stated that the respondents' answers to the questions in the questionnaire were consistent and could be seen from the results of Cronbach’s Alpha. The next stage is the classical assumption test, multicollinearity test, heteroscedasticity test, and multiple linear regression test. In addition, hypothesis testing was carried out through the F-test, T-test, and coefficient of determination. The results showed that financial capability and digital adoption had a significant influence on online shopping decisions.